Cohesive sediments in open channels : properties, transport, and applications - Partheniades, Emmanuel (Butterworth-Heinemann/Elsevier, 2009)
Control the impact of cohesive sediments on open channels by managing the effects of silt, clay and other sediments in harbors, estuaries and reservoirs. Cohesive Sediments in Open Channels provides you with a practical framework for understanding how cohesive sediments are transported, deposited and eroded. One of the first books to approach the subject from an engineering's perspective, this book supplies insight into applying hydraulic design as well as understanding the behavior of cohesive sediments in a flow field. Properties and of the nature and the origin of the interparticle physicochemical forces The forces between clay particles and the process of flocculation Processes and dynamics of flocculation and the hydrodynamic behavior of cohesive sediments Transport processes of sediments by flowing water and related equations are first presented and explained Deposition and resuspension of beds deposited from suspension from flowing waters Engineering applications of the hydraulics of cohesive sediments.
Keywords: Sediment transport.; Sediment control.; elektronické knihy; electronic books